Answer:
product of the roots= c/a
Explanation:
The the two roots(α and β) of the quadratic equation ax²+bx+c=0 as given by shridharacharya formula are
![\alpha= (-b+√(b^2-4ac) )/(2a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/6nz6ty6z08kj43lh068gk5g54to0e87bcs.png)
![\beta= (-b-√(b^2-4ac) )/(2a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/6vf6n6xrp9sw047rhyy1w36xyxyct7dyt3.png)
now product of the roots
αβ=
×
![(-b-√(b^2-4ac) )/(2a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/4g4v33i3xl1bpj85adw9ef4ik0q505384c.png)
use formula (a+b)(a-b)= a^2-b^2 and solve we get
αβ= c/a
therefore product of the roots= c/a